Death Anxiety and Depression in Amyotrophic Lateral Sclerosis Patients and Their Primary Caregivers - Grabler, Marvin R.; Weyen, Ute; Juckel, Georg; Tegenthoff, Martin; Mavrogiorgou-Juckel, Paraskevi (Frontiers in Neurology, 2018)
Background: Given the lethal severity of amyotrophic lateral sclerosis (ALS), the aim of this study was to illuminate the coherence of depression and death anxiety in both ALS patients and caregivers and in how far patients and caregivers are influenced by the mindset of their respective counterpart. Methods: 30 couples of patients (mean age 60.57; 13 women, 17 men) and primary caregivers (mean age 57.33; 16 women, 14 men) were included into the study. Death anxiety was assessed using the newly developed BOFRETTA scale, depression via Beck Depression Inventory, anxiety by means of State Trait Anxiety Inventory and caregivers’ exertion using the Caregiver Strain Index. Patients’ impairment was assessed with the ALS functional rating scale. Results: We found that while death anxiety was related to depression in both patients and caregivers, death anxiety was related to anxiety only in patients. Caregiver strain correlated with both caregiver`s depression and anxiety. Moreover, patients’ and caregivers’ depression, anxiety and death anxiety correlated to the ones of their counterpart. Conclusion: These results suggest that despite little depressive symptoms in ALS patients the fatal prognosis of the disease takes into account, depression and death anxiety influence each other and might be addressed together in pharmacological and especially psychotherapeutic interventions to the benefit of the patient. Besides, medical professionals should not forget to offer sufficient support to caregivers tending patients affected by depression and death anxiety as they are likely to mirror their patient’s feelings.